EFFECT OF CULTURE CONDITIONS FOR ANTIMICROBIAL ACTIVITY OF MARINE - DERIVED FUNGUS ASPERGILLUS FLOCCULOSUS 01NT.1.1.5 - Hoai Trinh, Phan Thi; Duy Ngoc, Ngo Thi; Dieu Trang, Vo Thi; Tien, Phi Quyet; Ly, Bui Minh; Thanh Van, Tran Thi; Thinh, Pham Duc; San, Pham Trung (Vietnam Journal of Biotechnology, 2018)
The biosynthesis of compounds with antibiotic activity produced by marine fungi, strongly depends on their growth conditions. A good understanding of the role of culture conditions in the biosynthesis of metabolites may lead to better exploitation of microbial metabolites. In this study, the influence of culture conditions including incubation period, initial pH and salinity on antimicrobial activity and secondary metabolites production of marine fungus 01NT.1.1.5 was investigated. This isolate, obtained from sponge Stylissa sp. in Nha Trang Bay, exhibited a broad spectrum of in vitro antimicrobial activity to Bacillus cereus ATCC 11778, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Listeria monocytogenes ATCC 19111, Streptococcus faecalis ATCC 19433 and Candida albicans ATCC 10231. According to morphological characteristics and sequence analysis of 28S rDNA, the fungus was identified as Aspergillus flocculosus. The results indicated that antimicrobial activity and metabolite amount were highest when the fungus was cultivated in rice medium with incubation period of 20 days. The optimum salinity of 35 g/L and initial pH of 6.0 were found for the maximum antibiotic production. The colony growth, antimicrobial activity and production of secondary metabolites of the strain A. flocculosus 01NT.1.1.5 varied depending on salt concentrations and initial pH of medium. Particularly, extract of this fungus only showed activity against C. albicans when it was cultured in medium with 30-35 g/L salinity and initial pH 4.0-8.0. The results indicate that salinity and initial pH along with cultivation period are important factors inﬂuencing antimicrobial activity and secondary metabolites of A. flocculosus 01NT.1.1.5, and might be for other marine fungi.